Analisis Visual Efek Khusus Dalam Film Fantasi: Studi Kasus Pada Film Spider-man: No Way Home: Teori Compositing Digital Dalam Menganalisis Visual Efek Film Fantasi - Adi, Reza Syahputra; Wulandari, Yulianti Fajar; Himawan, Sultan (Brand Communication, 2024)
This reserach aims to analyze visual special effects in fantasy films with a focus on the film "Spider-Man: No Way Home". Compositing theory and a qualitative methodology were employed in this study. This film was chosen as a case study because of its complex and innovative use of visual effects. This research uses visual analysis methods to identify the special effects visual elements used in this film. Compositing theory is used to understand how various visual elements are combined to create complex and realistic scenes. The use of CGI technology in films is also analyzed to reveal its impact on the viewing experience. The analysis results show that the use of visual special effects in "Spider-Man: No Way Home" is very successful in creating an immersive fantasy world for the audience. The combination of digital characters with real backgrounds gives a real and stunning impression. In addition, CGI technology has made it possible to create spectacular and stunning action scenes. In conclusion, the film "Spider-Man: No Way Home" is an excellent example of the application of visual special effects in the fantasy genre. The use of qualitative methods and compositing theory in this analysis provides a deep understanding of the complexity of the techniques used to create the stunning visual effects in this film.